The client - Grisham, John (Random House, 1993)
In a weedy lot on the outskirts of memphis, two boys watch a shiny Lincoln pull upt ot the curb... Eleven-year-old Mark Sway and his younger brother were sharing a forbidden cigarrette when a chance encounter with a suicidal laywer left Mark knowing a bloody and explosive secret: the whereabouts of the most sought-after dead body in America. Now Mark is caught between a legal system gone mad and a mob killer desperate to cover up his crime. And his only ally is a woman named Reggie Love, who has been a lawyer for all of four years. Prosecutors are willing to break all the rules to make Mark talk. The mob will stop at nothing to keep him quiet. And Reggie will do anything to protect her client -- even take a last, desperate gamble that could win Mark his freedom... or cost them both their lives.